ARE STEM CELL MARKER EXPRESSION AND CD133 ANALYSIS RELEVANT TO DIFFERENTIATE COLORECTAL CANCER? - Leticia Elizabeth Augustin CZECZKO; Carmen Australia Paredes Marcondes RIBAS; Nicolau Gregori CZECZKO; Thelma Larocca SKARE; Camila Kienen YAMAKAWA; Guilherme GIONEDIS; Cecilia VASCONCELOS; Fabiola Pabst BREMER; Diogo Francesco CASTOLDI; Martin GASSER; Ana Maria WAAGA-GASSER (ABCD: Arquivos Brasileiros de Cirurgia Digestiva, 2021)
ABSTRACT Background: CD133 and AXL have been described as cancer stem cell markers, and c-MYC as a key regulatory cellular mechanism in colorectal cancer (CRC). Aim: Evaluate the prognostic role of the biomarkers CD133, AXL and c-MYC and their association with clinicopathologic characteristics in colorectal adenocarcinomas and adenomas. Methods: A total of 156 patients with UICC stage I-IV adenocarcinomas (n=122) and adenomas (n=34) were analyzed. Tissue microarrays (TMA) from primary tumors and polyps for CD133, c-MYC and AXL expression were performed and analyzed for their significance with clinicopathologic characteristics. Results: Poorly differentiated adenocarcinomas and disease progression were independent risk factors for poor overall survival. The median overall survival time was 30 months. Positive CD133 expression (35.9% of all cases), particularly of right-sided CRCs (44.8% of the CD133+ cases), was negatively correlated with death in the univariate analysis, which did not reach significance in the multivariate analysis. c-MYC (15.4% of all cases) was predominantly expressed in advanced-stage patients with distant (non-pulmonary/non-hepatic) metastasis. AXL expression was found only occasionally, and predominantly dominated in adenomas, with less penetrance in high-grade dysplasia. Conclusions: CD133 expression was not associated with inferior overall survival in CRC. While AXL showed inconclusive results, c-MYC expression in primary CRCs was associated with distant metastasis.